2010
DOI: 10.1890/08-2370.1
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic basis for underyielding in phytoplankton communities

Abstract: Species richness has been shown to increase biomass production of plant communities. Such overyielding occurs when a community performs better than its component monocultures due to the complementarity or dominance effect and is mostly detected in substrate-bound plant communities (terrestrial plants or submerged macrophytes) where resource use complementarity can be enhanced due to differences in rooting architecture and depth. Here, we investigated whether these findings are generalizeable for free-floating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 48 publications
(50 reference statements)
3
52
1
Order By: Relevance
“…This effect agrees with experimental studies which observed an underyielding of diverse communities compared to their component monocultures due to the competitive suppression of highly productive species. [64][65][66][67] In this paper, we present a more comprehensive study of the model's behaviour, and the insights this can lead to with regard to the mechanisms under investigation. We present and discuss results related to pattern formation, population dynamics, the effects of more than one demographic process being simultaneously substrate-limited, and the effect of resource dependence on the system's critical mobility rate.…”
Section: Resultsmentioning
confidence: 99%
“…This effect agrees with experimental studies which observed an underyielding of diverse communities compared to their component monocultures due to the competitive suppression of highly productive species. [64][65][66][67] In this paper, we present a more comprehensive study of the model's behaviour, and the insights this can lead to with regard to the mechanisms under investigation. We present and discuss results related to pattern formation, population dynamics, the effects of more than one demographic process being simultaneously substrate-limited, and the effect of resource dependence on the system's critical mobility rate.…”
Section: Resultsmentioning
confidence: 99%
“…In order to identify potential mechanisms behind community responses, we compared Our results match other findings that the dynamics of single species do not always correlate predictably with their dynamics when in a group (Fridley 2002;Schmidtke et al 2010). One reason could be that the dynamics of the isolates depends on whether other species are present; for example through quorum sensing bacteria can alter the chemicals that they produce (Miller & Bassler 2001) or alternatively species may rely on the presence of others to obtain resources (Lawrence et al 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Underyielding (i.e., when a polyculture yields less than the average of its component monocultures) can result, for example, when a polyculture is dominated by a fast-growing, low-yielding species [14,24] or due to allelopathy, where a secondary metabolite produced by one species is toxic to another [36]. In order to maximize the potential for overyielding, polycultures can be assembled based on their specific traits (e.g., light, nitrogen, micronutrients, etc.)…”
Section: Ecological Principles and Polyculturesmentioning
confidence: 99%
“…Specific interactions of concern include competition, predation (i.e., grazing pressure), and pathogenic interactions. Competition for nutrients and allelopathy (chemical warfare) with non-target algal strains can significantly reduce production rates and/or alter the quality of the biomass produced [14,15]. Predation by grazers or invasion by algal pathogens can decrease the stability of production by destroying mass cultures in a matter of days [16].…”
Section: Introductionmentioning
confidence: 99%